Das políticas educacionais inclusivas bilíngues para surdos às políticas bilíngues de/com surdos: um estudo de caso - Bonfim, Tatiane Cristina (2020)
Bilingual education for the deaf is a right supported by legal documents, which should be implemented through public policies aimed at education. Such a proposal has to be expressed in each municipality, which builds specific actions for its production. It happens that each municipality presents different understandings of what it is to make a bilingual education and of how to promote the teaching in Brazilian Sign Language (Libras). The present study aimed to analyze the transposition of the discourses of truth about the education of deaf people and their implications to the daily practices of the Educational Interpreter (EI). To this end, we analyzed the guidelines regarding public policies of bilingual education for the deaf, implemented by the Department of Education of a municipality in the countryside of the state of São Paulo, in the early years of elementary school, as a component of knowledge of the investigated scenario and the daily practices implemented by educational interpreters in this educational unit. We used the analytical triangulation carried out through theoretical reflections and documentary analyses aligned with the conceptions of the participants. To this end, we crossed in the text the emerging statements of educational interpreters, teachers, school managers, and the Special Education Coordination. Such knowledge grounds the analyses aligned with the studies of legal devices in dialogue with the knowledge proposed by the philosophies of difference. The methodological proposal is consistent with the archogenealogical perspective of Michel Foucault. In summary, the research is described as a case study of a qualitative approach, with data crossed by the Deaf Studies and the philosophies of difference, in Michel Foucault. As a result of the study, we highlight the understanding that the daily practices of the educational interpreters still reflect a complex inclusive educational paradox: sometimes, we can see practices that point towards the education of/with the deaf and others, education for the deaf, namely, oriented by a hearing logic linked to the adequacy and repair of teaching to the deaf. There are existing disparities and internal struggles waged by the educational interpreters that reflect resistance against the logic of biopolitics produced in bilingual education, still aligned with the radical inclusion of figures, based on the erasure of multiplicity and deaf differences. The act of counter-action, daily promoted by these professionals in their minor actions, points to the first signs of the construction of education of/with deaf, based on legal devices, that even with limitations, can guide a bilingual perspective in Libras, focused on the desire of the deaf community for a singular education of/with the deaf.